An improved synthesis of the [5.6.7]-tricyclic core of cyrneine B and glaucopine C. Issue 19 (7th September 2020) - Wu, Guo-Jie; Han, Xiu
Abstract : A strategically new route for an efficient synthesis of [5.6.7]-tricyclic 9, which could serve as an advanced intermediate, was presented. Abstract : A new route for the synthesis of the [5.6.7]-tricyclic core structure of cyrneine B and glaucopine C is presented. The key transformations included an efficient Suzuki cross-coupling of the densely substituted cyclopentenyl triflate with cyclic vinylboronate and a highly regio- and stereoselective intramolecular deconjugative alkylation. The synthetic route allowed for the construction of the [5.6.7]-tricyclic core within a 16-step linear sequence from the commercially available 2-methylcyclopentanone, which is five steps shorter than the first generation route as reported previously by us.